2017
DOI: 10.1177/0022343316684009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting local violence

Abstract: Riots, murders, lynchings, and other forms of local violence are costly to security forces and society at large. Identifying risk factors and forecasting where local violence is most likely to occur should help allocate scarce peacekeeping and policing resources. Most forecasting exercises of this kind rely on structural or event data, but these have many limitations in the poorest and most war-torn states, where the need for prediction is arguably most urgent. We adopt an alternative approach, applying machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…We are particularly effective at identifying "hot spots" with high concentrations of violence, defined as five or more incidents in a single year. Indeed, our ensemble model, which leverages the best new methods, performs better than previous sub-national attempts (Blair et al, 2017;Colaresi et al, 2016;Weidmann and Ward, 2010;Witmer et al, 2017).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…We are particularly effective at identifying "hot spots" with high concentrations of violence, defined as five or more incidents in a single year. Indeed, our ensemble model, which leverages the best new methods, performs better than previous sub-national attempts (Blair et al, 2017;Colaresi et al, 2016;Weidmann and Ward, 2010;Witmer et al, 2017).…”
Section: Introductionmentioning
confidence: 82%
“…While LASSO penalizes the sum of the absolute value of the regression coefficients, ridge regression penalizes the sum of squares. We follow best practices as in Blair et al (2017) and use a weighted average of the two penalties, where the weight for the LASSO penalty is α = 0.95 and the weight on the ridge penalty is 1 − α.…”
Section: B Methodological Detailsmentioning
confidence: 99%
“…We are particularly effective at identifying "hot spots" with high concentrations of violence, defined as five or more incidents in a single year. Indeed, our ensemble model, which combines the best new methods, performs better than previous subnational attempts (Blair et al, 2017;Colaresi et al, 2016;Weidmann and Ward, 2010;Witmer et al, 2017). 2 We view these results as especially important given that such local hot spots can pose a serious risk of regional or national escalation, and some of these locations will not be known to policymakers, especially in large, diverse countries.…”
Section: Introductionmentioning
confidence: 86%
“…The previous related studies primarily involved research from three aspects, as shown in Table 1. A terrorist attack prediction project led by Blair et al used a neural network to successfully predict the conflict in Liberia in 2010 with the data in 2008; the accuracy was between 0.65 and 0.74 [19]. Dong used the 2010-2016 forecast of terrorist attacks in India as an example to empirically examine the effectiveness of machine learning based on back propagation (BP) neural networks in real-life terrorist attacks.…”
Section: Related Workmentioning
confidence: 99%